Estrategias de comunicación para el fortalecimiento de la identidad corporativa en la Radio Comunitaria Salinerito 89.9 FM, año 2023 - Dishu Espinoza, Felix Eliseo (2024)
present research work deals with communication strategies to strengthen the corporate identity of community radio Salinerito 89.9FM, the general objective was to design a comprehensive communication strategy aimed at effectively strengthening the corporate identity of community radio Salinerito 89.9 FM during the period 2023. The methodology used was based on a non-experimental cross-sectional design with descriptive and field research. The approach was mixed and the information collection technique was the survey through a 10-question multiple choice and closed questionnaire that was applied to a sample of 374 people who live in the rural parish of Salinas in the Guaranda canton. The main results indicated that there is a smaller but important percentage of radio-listening inhabitants who listen to the radio between 1 hour and 3 hours, so they do not feel identified with the organizational philosophy of this station, which is why they do not actively participate in the events that is promoted for the benefit of the community. The conclusions determined the need to strengthen the corporate identity of Salinerito community radio. Therefore, the design of a digital communication strategy is proposed to strengthen the corporate identity, adapted to the needs and interests of the radio station, to maintain greater interaction with its audience, planning joint actions and key material for